Coinfection of cotton plants with cotton leafroll dwarf virus atypical and a novel cotton begomovirus - Delfosse, Veronica Cecilia (2024)
Cotton is a commercial crop of global importance whose versatile fibre is widely used in the textile industry. Cotton is vulnerable to infectious pathogens, including viruses, that are a major threat to cotton production. Cotton blue disease is caused by cotton leafroll dwarf virus (CLRDV), a polerovirus transmitted by aphids. This virus is controlled by sowing cotton varieties resistant to CLRDV, although, in recent years an atypical variant (CLRDV-at), that breaks the resistance, has been identified. An outbreak of a disease occurred in cotton fields of the province of Chaco, in the north-west of Argentina, in the 2014–2015 growing season. NuOpal cotton plants (a variety resistant to CLRDV and susceptible to CLRDV-at) showed mosaic symptoms and had virus-transmitting insect vectors, such as aphids and whiteflies (Bemisia tabaci). The symptoms were common for virus infections but different from those caused by CLRDV or CLRDV-at. According to a reverse transcription-PCR analysis with polerovirus primers and sequencing, the plants contained CLRDV-at. To identify the complete virome of these plants, we performed a massive RNA-based deep sequencing assay using Illumina technology. As a result, a new begomovirus that infects cotton in Argentina was identified. Structural and functional annotation indicated that its sequences corresponded to complete DNA components A and B of a novel New World bipartite begomovirus. Genetic distance and evolutionary analyses support that the detected sequences correspond to a new virus, which we propose to name cotton mosaic virus (CoMV). In addition, we report the first begomovirus and polerovirus coinfection in cotton.